2019
DOI: 10.2217/fmb-2018-0314
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus DNA Sequences in the Blood of Healthy Population of Pakistan

Abstract: Aim: This study aimed at detecting and quantifying Merkel cell polyomavirus (MCPyV) viral loads in the peripheral blood of healthy Pakistani individuals. Patients & methods: A total of 221 whole blood samples obtained from healthy individuals were examined by qPCR. Results & conclusion: MCPyV was detected in the peripheral blood of 31.2% healthy individuals. The rate of MCPyV positivity decreased from young (36%), to middle (33.7%) and elder (25.3%) age groups. Our data revealed higher prevalence of MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The presence of MCPyV DNA, showing variable viral loads by the PCR technique, has also been described in several non-tumor tissues, such as skin, peripheral blood, gastrointestinal, respiratory, and urinary tracts, adrenal gland, spleen, bone marrow, stomach, gallbladder, pancreas, heart, and aorta, albeit with a relatively low viral load, between 0.00026 and 0.22 copies per cell. 27 , 28 , 29 , 30 On average, the number of copies of the MCPyV viral genome was 60 times lower in healthy tissues, when compared to MCC samples. 28 …”
Section: History Of Polyomavirus and Merkel Cell Polyomavirusmentioning
confidence: 97%
“…The presence of MCPyV DNA, showing variable viral loads by the PCR technique, has also been described in several non-tumor tissues, such as skin, peripheral blood, gastrointestinal, respiratory, and urinary tracts, adrenal gland, spleen, bone marrow, stomach, gallbladder, pancreas, heart, and aorta, albeit with a relatively low viral load, between 0.00026 and 0.22 copies per cell. 27 , 28 , 29 , 30 On average, the number of copies of the MCPyV viral genome was 60 times lower in healthy tissues, when compared to MCC samples. 28 …”
Section: History Of Polyomavirus and Merkel Cell Polyomavirusmentioning
confidence: 97%
“…Physiological immune impairment as a result of aging, or immunosenescence, could therefore favor high levels of MCPyV replication, ultimately leading to MCC onset. It has been reported that MCPyV viral load increases among elders, suggesting an age-related association of viral replication in the host ( 34 , 48 ). Considering these aspects, assessing the impact of MCPyV infection in various immunocompromised groups, including elders, can improve early identification of individuals at risk of developing MCC.…”
Section: Introductionmentioning
confidence: 99%